The Words of Boko HaramUnderstanding Speeches by Momammed Yusaf and Abubakar Shekau - (:unkn) unknown (My University, 2016)
Since the early 2000s, two preachers in northeastern Nigeria’s Borno State, Mohammed Yusuf and Abubakar Shekau, have deployed political and religious discourse to shape and promote the ideology of a movement commonly labelled “Boko Haram.” Their sermons and messages constitute a vast corpus of primary source documents; these precious tools shed light on the movement’s dynamics, revealing essential contextual elements that help us understand the Boko Haram phenomenon. The author draws on these rarely used, translated, and decoded extracts of speeches—practically the only available sources on the group’s discourse—to analyze the words of Boko Haram, paying attention to what is said to better understand the dynamics of current events.
Keywords: African Research